Les opérations policières à Rio de Janeiro (2007-2020): de l’inefficacité programmatique à la visée stratégique - Hirata, Daniel (Déviance et société, 2023)
Based on an analysis of police raids in favelas controlled by armed criminal groups, this article discusses how violence and politics are articulated in Rio de Janeiro, Brazil. The armed incursions conducted by police forces in poor neighborhoods are the main instrument of public action to control crime and are responsible for the greater part of the exorbitant number of killings by police officers on duty. Through comparing data on police raids, crime notifications and the map of armed groups in Rio de Janeiro, it was found that police raids do not contribute to reducing crime and that they are concentrated in areas controlled by a particular armed group (the ‘militias’) composed of police officers close to drug dealers whose operational expansion is thus facilitated. Based on these data, it is argued that the inefficiency of the operations constitutes a political agenda, instrumentalized as a strategy in the local power games to influence national politics.